GnRH agonist use for fertility preservation despite gonadotoxic chemotherapy - Blumenfeld, Zeev (Henry Stewart Talks, 2019)
Preservation of fertility in women undergoing gonadotoxic chemotx., Methods of fertility preservation, The rationale of ovarian suppression by GnRHa for fertility preservation, The efficacy of GnRHa, The safety of GnRHa, The GnRHa debate (why?), Possible mechanisms of GnRHa beneficial effect(s) for fertility preservation